2018
DOI: 10.1021/acs.nanolett.8b04398
|View full text |Cite
|
Sign up to set email alerts
|

Direct Probe of the Seebeck Coefficient in a Kondo-Correlated Single-Quantum-Dot Transistor

Abstract: We report on the first measurement of the Seebeck coefficient in a tunnel-contacted and gate-tunable individual single-quantum dot junction in the Kondo regime, fabricated using the electromigration technique. This fundamental thermoelectric parameter is obtained by directly monitoring the magnitude of the voltage induced in response to a temperature difference across the junction, while keeping a zero net tunneling current through the device. In contrast to bulk materials and single molecules probed in a scan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 52 publications
4
51
0
Order By: Relevance
“…Our theory also allows to explain the results shown in figure 4(a) of a recent experimental paper [29], albeit with a notable exception. These authors have found 'striking' sign changes of the Seebeck coefficients, in addition to the standard sign change at the particle-hole symmetric point.…”
Section: Linear and Nonlinear Thermopower And The Role Of Asymmetrysupporting
confidence: 57%
See 3 more Smart Citations
“…Our theory also allows to explain the results shown in figure 4(a) of a recent experimental paper [29], albeit with a notable exception. These authors have found 'striking' sign changes of the Seebeck coefficients, in addition to the standard sign change at the particle-hole symmetric point.…”
Section: Linear and Nonlinear Thermopower And The Role Of Asymmetrysupporting
confidence: 57%
“…These sign changes depend on the spin configuration of the quantum dot and are observed with increasing temperature. In the experiment [29], S in fact changes sign at three values of the gate voltage, with one of them at the particle-hole symmetric point. Two other gate voltages at which sign changes appear are related to consecutive energy levels crossing the chemical potential.…”
Section: Linear and Nonlinear Thermopower And The Role Of Asymmetrymentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, the Kondo effect has attracted attention in the context of the thermoelectric response of gatetunable semiconductor and molecular quantum dots, both experimentally [24][25][26] and theoretically [27][28][29][30][31][32][33] . Understanding the thermoelectric properties of such systems is important for using nanoscale thermoelectric elements to improve the energy efficiency of microelectronic devices [34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%